Fetal intrapericardial teratomas - Yuan, Shi-Min; Lin, Hong (The Turkish Journal of Pediatrics, 2019)
Fetal intrapericardial teratomas are rare and benign. However, they can be life-threatening owing to the complicated massive pericardial effusions, tamponade, or cardiorespiratory distress. The purpose of this review is to give an overview on clinical features, management and prognoses of fetal intrapericardial teratomas. The materials of this study were based on a comprehensive literature retrieval of fetal intrapericardial teratomas published in the past two decades. It was noteworthy that fetal pericardial/pleural effusions or ascites were detected since 19-week gestation, and tumors could be found since 21-week gestation. A growing trend of tumors was observed in more than half of the cases. Prenatal centesis and postnatal tumor resection were required in most of the cases. Fetoneonatal deaths (including fetal demise, termination of pregnancy and neonatal death) occurred in one-third of the cases. The neonatal survival rate was 59.4%. Symptomatic fetuses usually required perinatal maneuvers, such as pericardiocentesis, or thoraco-/ pericardio-amniotic shunt in order to improve fetal hemodynamic status and prolong the pregnancy for lung maturity. Open fetal surgery and ex utero intrapartum treatment (EXIT) procedure can be considered, however, impact of EXIT procedure on later delivery remains uncertain. Postnatal operation is a curative and symptom-relieving method for those cases with prenatally diagnosed intrapericardial teratomas. As a result, the fetoneonatal outcomes are somewhat promising.